2011
DOI: 10.1016/j.ydbio.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Reversible response of protein localization and microtubule organization to nutrient stress during Drosophila early oogenesis

Abstract: Summary The maturation of animal oocytes is highly sensitive to nutrient availability. During Drosophila oogenesis, a prominent metabolic checkpoint occurs at the onset of yolk uptake (vitellogenesis): under nutrient stress, egg chambers degenerate by apoptosis. To investigate additional responses to nutrient deprivation, we studied the intercellular transport of cytoplasmic components between nurse cells and the oocyte during previtellogenic stages. Using GFP protein-traps, we showed that Ypsilon Schachtel (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 70 publications
2
99
0
1
Order By: Relevance
“…They reside within ribonucleoprotein complexes (mRNPs) containing proteins that repress mRNA translation until they reach their destination in the oocyte. Enrichment of mRNPs in the oocyte depends on the microtubule (MT) network extending from the oocyte into nurse cells and dynein-mediated transport to the oocyte, combined with diffusion and localized retention in the oocyte (Koch and Spitzer, 1983; Shimada et al, 2011; Theurkauf et al, 1993). The oskar mRNP is one such complex, and includes the initiation factor eIF4E, the Y-box protein Yps, and the RNA helicase Me31B (Nakamura et al, 2001; Nakamura et al, 2004; Wilhelm et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They reside within ribonucleoprotein complexes (mRNPs) containing proteins that repress mRNA translation until they reach their destination in the oocyte. Enrichment of mRNPs in the oocyte depends on the microtubule (MT) network extending from the oocyte into nurse cells and dynein-mediated transport to the oocyte, combined with diffusion and localized retention in the oocyte (Koch and Spitzer, 1983; Shimada et al, 2011; Theurkauf et al, 1993). The oskar mRNP is one such complex, and includes the initiation factor eIF4E, the Y-box protein Yps, and the RNA helicase Me31B (Nakamura et al, 2001; Nakamura et al, 2004; Wilhelm et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The following protein-trap lines were used: Vsg-GFP (CA7004), Oda-GFP (YD0523), RpL30-GFP (YB0151), Yps-GFP (ZCL1607) Quinones-Coello et al, 2007;Shimada et al, 2011). Protein-trap lines are available at Flytrap (http://flytrap.med.yale.edu/).…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…Imaging of Staufen (Stau), a protein associated with RNPs containing oskar mRNA, revealed that oskar mRNA is randomly transported on MTs in all directions with a weak posterior bias [53]. Interestingly, Shimada et al recently discovered that the mRNA-binding protein Ypsilon Schachtel (Yps) is transported via both MT-dependent and MT-independent mechanisms and this transport is regulated by nutrient availability and insulin signaling, possibly as part of a mechanism to preserve oocytes during periods of nutrient deprivation and allowing for rapid resumption of reproduction when conditions improve [56 ].…”
Section: Live Imaging Of Collective Border Cell Migrationmentioning
confidence: 99%